Values, virtues, and vices, Italian style Caesar, Dante, Machiavelli, and Garibaldi - Belliotti, Raymond A., 1948- (The Fairleigh Dickinson University Press Series in Italian Studies., 2020)
"Values, Virtues, and Vices, Italian Style is an interdisciplinary study that examines the lives and work of four historical figures: Caesar, Dante, Machiavelli, or Garibaldi, as well as Italian culture and the moral psychology of pride, arrogance, justification, excuse, repentance, and the concept of honor"--